Comparison of fibrin-based clot elasticity parameters measured by free oscillation rheometry (ReoRox(®)) versus thromboelastometry (ROTEM(®)) - Solomon, Cristina (Scand J Clin Lab Invest, 2015)
Background. Whole blood viscoelastic tests such as the fibrin-based thromboelastometry (ROTEM(®)) test FIBTEM are increasingly used in the perioperative setting to quickly identify deficits in fibrin quality, and to guide hemostatic therapy. The recently developed FibScreen2 test of the ReoRox(®) method, based on free oscillation rheometry, also provides an evaluation of fibrin clot quality. To date, little information is available on the performance of this test in hemodiluted blood, by comparison to FIBTEM. Methods. Whole blood samples from eight healthy volunteers were analyzed using FIBTEM and Fibscreen2. Native and diluted (to 33% and 50% using saline, gelatin or hydroxyethyl starch [HES]) samples were analyzed. Clot strength parameters, including FIBTEM maximum clot firmness (MCF), FIBTEM maximum clot elasticity (MCE) and Fibscreen2 maximum elasticity (G'max), were measured. Results. In repeatedly measured samples from two volunteers, FIBTEM MCF and Fibscreen2 G'max revealed a coefficient of variation (CV) of 5.3 vs. 16.3% and 5.6 vs. 31.7% for each volunteer, respectively. Hemodilution decreased clot strength. Both Fibscreen2 G'max and FIBTEM parameters decreased proportionally to the dilution ratio when saline was used. The observed reductions in FIBTEM and Fibscreen2 parameters were more severe in samples diluted with gelatin and HES, compared to saline. Finally, a regression analysis between FIBTEM MCE and Fibscreen2 G'max revealed a poor goodness of fit (r(2) = 0.37, p < 0.0001). Conclusions. ReoRox(®) Fibscreen2 test has a high coefficient of variation, and its application in various hemodilution conditions showed limited comparability with the ROTEM(®) FIBTEM test.